Pengaruh Work-Life Imbalance terhadap Kinerja Layanan Nasabah pada Karyawan Perbankan yang Berstatus Mahasiswa di Kota Bandung - Al Rasyid, Aly; Rafli Putra Pratama; Zalzabila Arzeta Putri; Mohammad Daffa Nugraha; Andre Suryaningprang (CV. ALIM'SPUBLISHING, 2026)
Abstract. This study aims to determine the effect of Work-Life Imbalance on Customer Service Performance among banking employees who are also university students in Bandung City. Dual roles as employees and students have the potential to create an imbalance between work and academic life, which may affect the quality of customer service. This study employed a quantitative approach with a sample of 25 respondents consisting of active banking employees who are currently pursuing higher education. Data were collected through questionnaires and analyzed using simple linear regression with the assistance of IBM SPSS software. The results indicate that Work-Life Imbalance has a significant effect on Customer Service Performance. The coefficient of determination (R Square) value of 0.837 shows that the Work-Life Imbalance variable explains 83.7% of the variance in Customer Service Performance, while the remaining percentage is influenced by other variables outside the scope of this study. Therefore, banking companies are expected to provide appropriate support for employees who carry dual roles as workers and students.